PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) MALAHAYATI ACEH DENGAN DISIPLIN KERJA DAN KOMITMEN ORGANISASI SEBAGAI INTERVENING VARIABEL - Harris R Dahlan; Nasir Azis; Nurdasila Darsono (Jurnal Magister Manajemen, 2018)
This study aims to examine and analyze the effect of job satisfaction on organizational discipline and commitment as well as its impact on the Performance of the Education and Training Center Students of the Shipping Sciences (BP2IP) Malahayati Aceh. Population in this research is all employees at Education and Training Center of Sailing Science (BP2IP) Malahayati Aceh that is 115 people. Sampling in this study using census method because it involves the entire population to respondents research. Data analysis technique used in this research is The Structural Equation Modeling (SEM) of statistical software package AMOS 22.0 for hypothesis testing. Proof of Hypothesis is done by using indicator of CR and P value. Because of the 5 verifikatif hypotheses tested in this study have CR value above 1.96 or P value smaller than 0.05, then all hypotheses tested reject Ho and receive H1. In other words, job satisfaction has an effect to improve employee performance as long as the independent variable can be improved by the management of Education and Training Center of Sea Sciences (BP2IP) Malahayati Aceh. The intervening variable that is discipline and organizational commitment has no influence to increase the dependent variable with other words meaning that the improvement of employee performance will be better done by increasing job satisfaction directly without including the variable of work discipline and organizational commitment